Determinan Penyerapan Tenaga Kerja Sektor Industri: Analisa Data Panel di Provinsi Jawa Barat - Pudjaningrum, Efrilizia Soraya; Athoillah, Moh. (Jurnal Dinamika Ekonomi Pembangunan, 2025)
This study aims to analyze the determinants affecting labour absorption in the industrial sector of West Java province. Using random effect panel data regression, it examines secondary data from 2017 to 2021. The findings indicate that city/regency minimum wages, economic growth, private sector investment, and the number of operating industries positively and significantly influence labour absorption in the industrial sector. Conversely, road infrastructure, foreign direct investment, and the education index do not show a statistically significant effect. To enhance economic growth and labour absorption, the government should accelerate investment, improve the ease of doing business, promote labour-intensive industries, and align labour market needs with industry demands through education and training programs.